Maurice Tardif - trajetória de um pesquisador: entre profissionalização do ensino, pensamento crítico e riscos contemporâneos 1 2 3 4 5 - Souza, Samuel De [UNESP] (2021)
This text presents the academic trajectory of the professor, intellectual and researcher Maurice Tardif from Université de Montréal (University of Montreal) in Canada, through an interview, conducted by Samuel de Souza Neto and Eliana Ayoub in May 2017. Maurice Tardif has been dedicating his reflections and researchers to educational themes related to teacher’s knowledge, to professional education, to division of work at school, as well as professional insertion and teaching professions in the school context. He discusses the professionalization of education, questioning the fact that this process does not emerge from teachers, but from state inductions or from movements for valorization of the magisterium, challenging teachers to fight for their own professional identity. To beyond the creation of research centers, as the Centre de Recherche Interuniversitaire sur la Formation et la Profession Enseignante (Crifpe – Interuniversity Research Center on Teacher’s Education and Profession), what is observed is the birth of a school of thought, the Quebec School on Teacher’s Education and Profession.